Tuberculous meningitis: where to from here? - Donovan, J; Thwaites, GE; Huynh, J (Wolters Kluwer Health, 2020)
PURPOSE OF REVIEW:Tuberculous meningitis (TBM) is associated with significant mortality and morbidity yet is difficult to diagnose and treat. We reviewed original research published in the last 2 years, since 1 January 2018, which we considered to have a major impact in advancing diagnosis, treatment and understanding of the pathophysiology of TBM meningitis in children and adults. RECENT FINDINGS:Studies have sought to identify a high sensitivity diagnostic test for TBM, with new data on modified Ziehl--Neelsen staining, urinary and cerebrospinal fluid (CSF) lipoarabinomannan and GeneXpert Ultra. Recent studies on CSF biomarkers provide a better understanding of the detrimental inflammatory cascade and neuromarkers of brain damage and suggest potential for novel host-directed therapy. Tryptophan metabolism appears to affect outcome and requires further study. Increased clinical trials activity in TBM focuses on optimizing antituberculosis drug regimens and adjuvant therapy; however, there are few planned paediatric trials. SUMMARY:Tuberculous meningitis still kills or disables around half of sufferers. Although some progress has been made, there remains a need for more sensitive diagnostic tests, better drug therapy, improved management of complications and understanding of host-directed therapy if outcomes are to improve.